Improvement in radiodiagnosis of vesicoureteral reflux in children - Sharofiddinov Alisher; Islamov Rasuljon; Zulunov Azizbek (Zien Journals, 2022)
This study aimed to identify the differences between primary and secondary vesicoureteral reflux (VUR) and the effect of associated bladder abnormalities on kidney function. We retrospectively reviewed the medical records of children with VUR who were followed up at Andijan state medical Institute Hospital. The review included results of radiological investigations and kidney function tests.
Keywords: Neurogenic bladder; primary reflux; vesicoureteral reflux